Relationship Between Stage of Gonad Maturity and Level of Osmotic Work of Sea Cucumber, Paracaudina australis - Widianingsih Widianingsih; Muhammad Zainuri; Sutrisno Anggoro; Hermin Pancasakti Kusumaningrum; Retno Hartati (Marine Science Department Diponegoro University, 2018)
The holothuroid spawning can be succesful depend on varoius factors such as salinity, temperature, primary productivity and other physiological adaptation toward environment influences. The salinity fluctuation is one of the environment factors, which influence and can cause various osmotic pressure of coelomic fluid of Holothoroid and also gonad maturity stage. Holothuroid (sea cucumber), Paracaudina australis, is overexploited in Kenjeran waters, Surabaya, East Java. The study was aimed to reveal relationship between gonad maturity stage and level of osmotic work of sea cucumber P. australis. Fifty samples of P. australis were collected monthly. Coelomic fluid samples of approximately 200–1000 µl were obtained from all samples using disposable insulin syringes. There were 37 holothuroids classified in the late maturity (stage 5), 74 holothuroid in the earlier maturity stage (stage 1). Gonad maturity stage 5 (late maturity) could be reached on December 2016. Contrasly, the gonad maturity stage 1 (earlier maturity) was found on August 2016. The analysis of coelomic fluid showed that the average value of level of osmotic work ranged 70 to 91 mOsm/L H2O in the earlier gonad maturity stage. Contrasly, in the late maturity, the average value of level of osmotic work ranged 118 to 156 mOsm/L H2O. There is relationship between gonad maturation stage and level of osmotic work. From stage of gonad maturity 1 to 5, there were upward trend level of osmotic work in coelomic fluid of P. australis.